Numerical Modeling of Rock Panels Subjected to Blast Loadings - Haijun Wang; Daiyu Xiong; Yun Duan; Weiqin Cao; Wenru Zhang; Peng Jiao; Bonan Wang; Xulin Zhao; Yonggang Miao; Le Zhou (Advances in Civil Engineering)
In rock engineering problems, the rock is usually subjected to dynamic loads induced by drill, blast and rockburst. Therefore, understanding the dynamic response of rock benefit the safety and productivity of excavation activities. In this study, the response of rock panels under blast loadings is numerically investigated. The uniaxial and triaxial compression tests are firstly conducted in the laboratory to obtain the material property of four types of rocks, including Chuanshan limestone, Gaolishan sandstone, Mineralized limestone and Xixia limestone. Then, a total of 16 numerical simulations are carried out in which each type of rock panel is subjected to TNT blast loadings with four scaled distances, i.e., 0.15 m/kg1/3, 0.30 m/kg1/3, 0.60 m/kg1/3, 1.20 m/kg1/3. The damage distribution, which is characterized by the effective plastic strain, within the rock panels is quantitatively and qualitatively analyzed. The modelling results demonstrate that the effect of blast loading on the rock is material dependent. For a given scaled distance, the Gaolishan sandstone damages most severely, followed by Xixia limestone, Chuanshan limestone, and mineralized limestone. A critical scaled distance is observed on the limestone panels. When the scaled distance is smaller than the critical value, the damage of limestone panels increases with increasing the scaled distance. Once exceeding the critical value, the damage of limestone panels decreases with the increase of scaled distance. However, such a transitional scaled distance is not observed in the sandstone panels, of which damage decreases gradually with the increases of scaled distance.